Global impact of unconventional energy resources - Dorraj, Manochehr; Morgan, Ken M. (Lexington Books, 2019)
This volume presents the reader with a comprehensive account of the development of shale oil and gas reserves globally. This study provides a comparative perspective that enables readers to situate the unique US experience in a broader global context and appreciate the limitations of reproducing it elsewhere in the immediate future.